OPTIMALISASI BUDAYA K3 MELALUI EDUKASI TEKNIK ANGKAT YANG BENAR - Salsabila, Aulia; Rosadi, Rakhmad (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2025)
Occupational Safety and Health (K3) is an important effort to prevent workplace accidents and maintain the physical and mental health of workers to increase productivity. One of the risks that often occurs in the workplace is musculoskeletal disorders due to unergonomic lifting activities. K3 physiotherapy plays a promotive and preventive role through ergonomic education, improving work posture, and training in correct lifting techniques. This community service activity aims to increase workers' knowledge of correct lifting techniques through the application of the diagonal lift method. The methods used include education using posters, practical demonstrations, and discussion sessions for five ceiling shop workers in Sidorame, Barengkrajan, Krian District, Sidoarjo Regency. Evaluation was carried out through pre-tests and post-tests to determine the level of knowledge of the participants. The pre-test results showed that most participants still had low knowledge regarding correct lifting techniques. After being provided with education, the post-test results showed a significant increase in knowledge, where all participants were able to answer questions correctly. In addition, practical observations showed improvements in work posture such as keeping the back neutral, bending the knees when lifting, and bringing the load closer to the body so that it is safer for the musculoskeletal system.